(NpOGOUVENIE W MUZYKU ILI(B. (NtAJNY GENIEW(B-2s (NLEKCIJs - (NmIHAIL kAZINIK(B.s ((NmOSKWAs (Nasts, 2019)
(NmIHAIL kAZINIK(B- (NISKUSSTWOWED MUZYKANT(B, (NPISATELX(B, (NPO\T(B, (NFILOSOF(B, (NREVISSER(B,(NAKTER(B, (NDRAMATURG(B, (NPROSWETITELX ODIN IZ SAMYH \RUDIROWANNYH L@DEJ NA[EGO WREMENI(B.s
Keywords: (NmONOGRAFIQs